Can bitcoin replace gold in an investment portfolio? - Irene Henriques; Perry A. Sadorsky (Journal of Risk and Financial Management, 2018)
Bitcoin is an exciting new financial product that may be useful for inclusion in investment portfolios. This paper investigates the implications of replacing gold in an investment portfolio with bitcoin ('digital gold'). Our approach is to use several different multivariate GARCH models (dynamic conditional correlation (DCC), asymmetric DCC (ADCC), generalized orthogonal GARCH (GO-GARCH)) to estimate minimum variance equity portfolios. Both long and short portfolios are considered. An analysis of the economic value shows that risk-averse investors will be willing to pay a high performance fee to switch from a portfolio with gold to a portfolio with bitcoin. These results are robust to the inclusion of trading costs.
Keywords: G11; G17; G32; 330; Bitcoin; gold; GARCH; portfolio modelling; risk management